STRESS, NUTRITION, AND SLEEP QUALITY AS DETERMINANTS OF MENSTRUAL CYCLE REGULARIY AMONG ADOLESCENTS - Nita Dwi Astikasari; Tety Ripursari (Journal for Quality in Women's Health, 2025)
Menstrual cycle irregularity is a common reproductive health issue among adolescents. Various factors, including psychological stress, nutritional status, and sleep quality, have been reported to Influence the regularity of the menstrual cycle. this studi to analize the relationship between stress levels, nutritional status, and sleep quality with menstrual cycle regularity in adolescents. The results, The study showed that 40% of respondents experienced irregular menstrual cycles. Stress was significantly associated with menstrual irregularity (p=0.002), adolescents with high stress were 3.1 times more likely to have irregular cycles. Poor nutrition was also correlated (p=0.015), with undernourished adolescents being 2.4 times more likely to experience irregular cycles. Poor sleep quality had a significant relationship as well (p=0.008), with poor sleepers being 2.9 times more likely to have irregular cycles.